Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Solve only in the Substitution method-3x + y = -24x - y = 4

Sagot :

The given equations are:

[tex]\begin{gathered} -3x+y=-2\text{ Eq(1)} \\ 4x-y=4\text{ Eq(2)} \end{gathered}[/tex]

Solve for y in terms of x in equation 1:

[tex]\begin{gathered} -3x+y=-2 \\ y=-2+3x\text{ Eq(3)} \end{gathered}[/tex]

Substitute y in equation 2:

[tex]\begin{gathered} 4x-(-2+3x)=4 \\ \text{Apply the distributive property} \\ 4x+2-3x=4 \\ x+2=4 \\ x=4-2 \\ x=2 \end{gathered}[/tex]

Now, substitute x in equation 3 and find y:

[tex]\begin{gathered} y=-2+3\cdot2 \\ y=-2+6 \\ y=4 \end{gathered}[/tex]

Thus, x=2 and y=4.